2005
DOI: 10.1128/jb.187.7.2386-2394.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the Acetate Binding Pocket in theMethanosarcina thermophilaAcetate Kinase

Abstract: Acetate kinase catalyzes the reversible magnesium-dependent synthesis of acetyl phosphate by transfer of the ATP ␥-phosphoryl group to acetate. Inspection of the crystal structure of the Methanosarcina thermophila enzyme containing only ADP revealed a solvent-accessible hydrophobic pocket formed by residues Val 93 , Leu 122 , Phe 179 , and Pro 232 in the active site cleft, which identified a potential acetate binding site. The hypothesis that this was a binding site was further supported by alignment of all ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 43 publications
1
43
1
Order By: Relevance
“…The extraordinarily broad acyl substrate range for EhACK and the strong preference for the acetate/PP i -forming direction suggest differences between EhACK and MtACK in acetate/acetyl phosphate binding. Acyl substrate binding in MtACK appears to be mediated primarily through hydrophobic interaction between the methyl group of acetate and residues within the acetate binding pocket, with the side chains of the binding pocket residues also serving to properly position the carboxyl group of acetate in proximity to the ␥-phosphate of ATP (13,17). Our results and those of IngramSmith et al (17) Pro variant showed a similar acyl substrate range and kinetic parameters to the unaltered enzyme in the direction of acyl phosphate formation.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The extraordinarily broad acyl substrate range for EhACK and the strong preference for the acetate/PP i -forming direction suggest differences between EhACK and MtACK in acetate/acetyl phosphate binding. Acyl substrate binding in MtACK appears to be mediated primarily through hydrophobic interaction between the methyl group of acetate and residues within the acetate binding pocket, with the side chains of the binding pocket residues also serving to properly position the carboxyl group of acetate in proximity to the ␥-phosphate of ATP (13,17). Our results and those of IngramSmith et al (17) Pro variant showed a similar acyl substrate range and kinetic parameters to the unaltered enzyme in the direction of acyl phosphate formation.…”
Section: Discussionsupporting
confidence: 78%
“…MtACK site-altered enzyme variants were produced and purified as previously described (16,17). Kinetic parameters in the acetate/ATP-forming direction of the reaction were determined using a coupled enzyme assay in which ATP formation was coupled to the reduction of NADP to NADPH (1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetate kinases are ubiquitous in the Bacteria, found in one genus of Archaea, and are also present in microbes of the Eukarya 6 . The most well characterized acetate kinase is that from the methane-producing archaeon Methanosarcina thermophila [7][8][9][10][11][12][13][14] . An acetate kinase which can only utilize PPi but not ATP in the acetyl phosphate-forming direction has been isolated from Entamoeba histolytica, the causative agent of amoebic dysentery, and has thus far only been found in this genus 15,16 .…”
mentioning
confidence: 99%